Pandemics and the environmental rebound effect: reflections from COVID-19 - Jaume Freire-González; David Font Vivanco (Environmental and Resource Economics, 2020)
The irruption of the COVID-19 pandemic has raised concerns on sustainability issues. The pandemic has accelerated the implementation of technologies such as ICT and shifts in mobility behaviour. Such changes have the potential to reduce environmental burdens, but also to trigger large environmental rebound effects. This perspective article reflects on some emerging concerns on the socio-economic effects of a pandemic on the environment from a rebound effect perspective. Although the pandemic offers potential to improve the environmental conditions, it brings also a high risk to produce Jevons' Paradox, i.e., increase environmental burdens rather than decrease them, as initially expected. Governments should be aware of these risks and assess the possibility to implement additional measures, like environmental taxation or limiting the use of resources, to help achieving sustainability targets.
Keywords: 330